If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3)(-2x + -7) = 0 Reorder the terms: (3 + x)(-2x + -7) = 0 Reorder the terms: (3 + x)(-7 + -2x) = 0 Multiply (3 + x) * (-7 + -2x) (3(-7 + -2x) + x(-7 + -2x)) = 0 ((-7 * 3 + -2x * 3) + x(-7 + -2x)) = 0 ((-21 + -6x) + x(-7 + -2x)) = 0 (-21 + -6x + (-7 * x + -2x * x)) = 0 (-21 + -6x + (-7x + -2x2)) = 0 Combine like terms: -6x + -7x = -13x (-21 + -13x + -2x2) = 0 Solving -21 + -13x + -2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '-1'. -1(21 + 13x + 2x2) = 0 Factor a trinomial. -1((7 + 2x)(3 + x)) = 0 Ignore the factor -1.Subproblem 1
Set the factor '(7 + 2x)' equal to zero and attempt to solve: Simplifying 7 + 2x = 0 Solving 7 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 0 + -7 2x = 0 + -7 Combine like terms: 0 + -7 = -7 2x = -7 Divide each side by '2'. x = -3.5 Simplifying x = -3.5Subproblem 2
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Solution
x = {-3.5, -3}
| x^2+px-p+2=0 | | 1/7x-4=-6/7x-5 | | 4x-4=10+3x | | r-65/3=6 | | 6w+w=56 | | 1/8(8x-6)=-1/4-9/4 | | 28+3p=56 | | 4x+6+2x=25+5x-7 | | 40=15u-7u | | 1900=10x+10y | | xyz=140 | | 5x+10=7-2 | | 3e^2x+5=1100 | | 10+3x=4x-11 | | 3x-2x=-12-4 | | 27-x=167 | | 9m-16=15 | | Y^2=4.8(x-1) | | 25-5x=x-5 | | x+15*x=100 | | 18n=64 | | -4k=-9+5k | | x=1/2(8x-24) | | 8x-3(2x-1)=2x+4 | | 8a^2+19a+6= | | 8q+9=5q | | 3n^2-25=0 | | 8x+3(2x-1)=2x+4 | | 2(13-x)=4(8-x) | | 7x-28/8x-48 | | 9-2k-3k=-1 | | x^2-8x+y^2-10y=-25 |